Implementasi Sistem Pengelolaan Management Resiko Untuk Perlindungan K3 Karyawan Perusahaan Berbasis Nilai Nilai Kebangsaan UUD 1945 di PT. Astra Honda Indonesia - Abram Tellurian Prastoto; Edy Soesanto; Lintang Septy Fauzan (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2024)
As the constitution of Indonesia, the 1945 Constitution (UUD 1945) serves as the basis for the drafting of laws governing various aspects of life, including health and occupational safety (K3). The 1945 Constitution does not explicitly regulate K3 but provides the foundation for the development of laws governing this field. Effective occupational health and safety (K3) practices help reduce workload and the risk of injuries in the workplace. This includes the identification, assessment, and control of potential hazards, as well as the enhancement of safety and health protection in the workplace. By implementing good K3 practices, companies can ensure that their employees work in safe and healthy environments, thus reducing workload and increasing productivity. The purpose of the study on Occupational Health and Safety (K3) Management and Workload is to analyze the relationship between K3 factors and employee workload, and to assess the impact of K3 programs on employee workload and overall health status. To address these challenges, collaborative efforts between the government, companies, labor unions, and K3 experts are required. Adequate resource provision, effective training, and inclusive safety culture promotion are key to enhancing K3 implementation. Additionally, technology can be utilized to strengthen risk monitoring and management systems in the workplace. In conclusion, the implementation of K3 in the workplace requires a comprehensive and sustainable approach to achieve a safe and healthy working environment for all employees. With strong cooperation among various stakeholders, it is hoped that a robust and sustainable safety culture can be established across various industrial sectors.